Berberine loaded glyceryl monooleate nanoparticles exhibited potent intrinsic anticancer activity against pancreatic cancer therapy: In vitro and in silico studies - Md․ Harun Al Rashid; Sweta Mishra; Saswati Pattnaik; Chandana Mohanty (Nano Trends)
Berberine (BER) has emerged as a promising anticancer medication that can induce antiproliferative effects in several cancers, including pancreatic cancer. However, its clinical application is limited by poor solubility and bioavailability. To overcome these challenges, BER-loaded glyceryl monooleate nanoparticles (BER-GNPs) were developed to enhance its delivery and therapeutic efficacy. The synthesized BER-GNPs were characterized using dynamic light scattering (DLS), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR), which confirmed their favorable size, morphology, and stability. In vitro studies demonstrated that BER-GNPs significantly increased cytotoxicity and inhibited cell migration and invasion in pancreatic cancer cells (PANC-1) compared to native BER. Furthermore, in silico studies suggested that BER may inhibit tumor cell proliferation by targeting the AKT signaling pathway. This was further validated through western blot analysis which confirmed that BER-GNPs significantly suppressed AKT phosphorylation and activated the intrinsic apoptotic pathway by increasing the Bax/Bcl-2 ratio, indicating enhanced pro-apoptotic activity.